2011
DOI: 10.1002/jsfa.4411
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical characterisation for industrial use of pomegranate (Punica granatumL.) cultivars grown in Spain

Abstract: These useful results can be employed by the juice processing industry to select those properties more interesting for the development of pomegranate juices that are organoleptically attractive and rich in bioactive compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
220
7
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(279 citation statements)
references
References 43 publications
50
220
7
2
Order By: Relevance
“…This range was smaller than that reported by Sepúlveda et al [64], 168-1328 mg Cy 3-glu/l, for genotypes of different regions of Chile. When comparing our results with Mena et al [3], a similar trend was obtained, namely: Wonderful > Mollar de Elche > Valenciana. In generally, our results were higher than Elfalleh et al [64] who reported values between 28.15 (Gabsi3) and 48.27 (Chetoui) mg Cy 3-glu/l for Tunisian cultivars.…”
Section: Total Monomeric Anthocyaninsupporting
confidence: 90%
See 2 more Smart Citations
“…This range was smaller than that reported by Sepúlveda et al [64], 168-1328 mg Cy 3-glu/l, for genotypes of different regions of Chile. When comparing our results with Mena et al [3], a similar trend was obtained, namely: Wonderful > Mollar de Elche > Valenciana. In generally, our results were higher than Elfalleh et al [64] who reported values between 28.15 (Gabsi3) and 48.27 (Chetoui) mg Cy 3-glu/l for Tunisian cultivars.…”
Section: Total Monomeric Anthocyaninsupporting
confidence: 90%
“…On the contrary, Tezcan et al [69] reported higher values than ours, namely 14.4-1008.6 mg GAE/100 ml. When comparing our results with Mena et al [3], who also studied Spanish cultivars, our value for Mollar de Elche was lower than theirs (94. …”
Section: Total Reducing Capacitysupporting
confidence: 49%
See 1 more Smart Citation
“…). In general the values obtained for all pomegranate juices were to those previously reported by Mena et al [22], which reported values in the range from 7.01 and 37.1 mmol Trolox L −1 .…”
Section: Total Phenolic Contentsupporting
confidence: 89%
“…The variability in the TPC values may be caused by reactions taken place during juice manufacture (i.e., hydroxylation, methylation, isoprenylation, imerization and/or glycosylation) [21]. The obtained TPC values were similar with those found by Mena et al [22] (1562 to 2342 mg GAE L −1 ) in "Mollar de Elche" and "Valenciana" cultivars. In a similar way, the farming type (organic or conventional) did not affect the TPC in orange juice [23].…”
Section: Total Phenolic Contentsupporting
confidence: 83%